Progress In Implementing The Framework For Enhanced Fund Engagement On Governance. (International Monetary Fund, 2020)
This paper provides an interim update on implementation of the 2018 Framework for Enhanced Fund Engagement on Governance. This update is in advance of a comprehensive formal review of the Framework scheduled for mid-2021.